Intrathecal HIV-1 Envelope Glycoprotein gp120 Induces Enhanced Pain States Mediated by Spinal Cord Proinflammatory Cytokines - Milligan, Erin D. (J Neurosci, 2001)
Perispinal (intrathecal) injection of the human immunodeficiency virus-1 (HIV-1) envelope glycoprotein gp120 creates exaggerated pain states. Decreases in response thresholds to both heat stimuli (thermal hyperalgesia) and light tactile stimuli (mechanical allodynia) are rapidly induced after gp120 administration. gp120 is the portion of HIV-1 that binds to and activates microglia and astrocytes. These glial cells have been proposed to be key mediators of gp120-induced hyperalgesia and allodynia because these pain changes are blocked by drugs thought to affect glial function preferentially. The aim of the present series of studies was to determine whether gp120-induced pain changes involve proinflammatory cytokines [interleukin-1β (IL-1) and tumor necrosis factor-α (TNF-α)], substances released from activated glia. IL-1 and TNF antagonists each prevented gp120-induced pain changes. Intrathecal gp120 produced time-dependent, site-specific increases in TNF and IL-1 protein release into lumbosacral CSF; parallel cytokine increases in lumbar dorsal spinal cord were also observed. Intrathecal administration of fluorocitrate (a glial metabolic inhibitor), TNF antagonist, and IL-1 antagonist each blocked gp120-induced increases in spinal IL-1 protein. These results support the concept that activated glia in dorsal spinal cord can create exaggerated pain states via the release of proinflammatory cytokines.